1999
DOI: 10.1007/s000240050321
|View full text |Cite
|
Sign up to set email alerts
|

Phase Space Structure, Attractor Dimension, Lyapunov Exponent and Nonlinear Prediction from Earth's Atmospheric Angular Momentum Time Series

Abstract: On a short time scale, Atmospheric Angular Momentum (AAM) has been demonstrated to be essentially the sole excitation source of LOD variations. The LOD variation, therefore, merely reflects the AAM variation (LOD as proxy for AAM). The study of the nonlinear nature of AAM variability (e.g., its orbital complexity, dimensionality and extreme sensitivity to the initial conditions) may provide a physical premise for theoretical modelling of the earth-atmosphere-ocean system. Analysis of the high quality of detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Stable or stochastic oscillations have a zero exponent, whereas chaotic systems show positive Lyapunov exponents. The use of this measure is widespread and has been used to reveal chaotic behavior in bacterial population dynamics (38), as well as economical and climatological systems (39,40). We analyzed 10 cells undergoing a mycorrhizal calcium response and found that 9 of the 10 cells showed positive Lyapunov exponents, indicating chaotic behavior (Fig.…”
Section: Rhizobial Bacteria and Mycorrhizal Fungi Induce Differentialmentioning
confidence: 99%
“…Stable or stochastic oscillations have a zero exponent, whereas chaotic systems show positive Lyapunov exponents. The use of this measure is widespread and has been used to reveal chaotic behavior in bacterial population dynamics (38), as well as economical and climatological systems (39,40). We analyzed 10 cells undergoing a mycorrhizal calcium response and found that 9 of the 10 cells showed positive Lyapunov exponents, indicating chaotic behavior (Fig.…”
Section: Rhizobial Bacteria and Mycorrhizal Fungi Induce Differentialmentioning
confidence: 99%
“…This particular method of nonlinear forecasting is relatively robust and works well on natural data. Several studies (MCCLOSKEY et al, 1991;MCCLOSKEY, 1993;TSONIS and ELSNER 1992;TIWARI and RAO, 1998) demonstrated the applicability of this technique for multidimensional data using the synthetic as well as actual time series, aiming to distinguish chaos from stochastic/random fractals.…”
Section: Nonlinear Forecasting Techniquementioning
confidence: 99%